CONSIDERATIONS REGARDING THE LEGAL NATURE OF THE DECISIONS AND/OR THE ORDERS OF THE UNIVERSITY ETHICS COMMISSIONS - Iulian BĂICULESCU (Challenges of the Knowledge Society)
One of the most important activities in a society is scientific research. Its essential character is conferred by its role in the perpetuation of social, economic and other human progress, all of which are underpinned by scientific progress. The functioning of the scientific research system is based, on the one hand, on a scale of academic degrees and diplomas designed to ensure and reward, gradually and thematically, an increased level of competence and complexity in the performance of scientific tasks and, on the other hand, the confidence of society as a whole in the quality and honesty of the holders of scientific degrees and diplomas. However, like any other area of economic and social life, scientific research is by its very nature perfectible. Or, to put it another way, it is subject to the permeability to various manifestations of unethical and deontological research activity. And this susceptibility is all the more present in developing societies, which have not yet achieved a sufficient degree of social and institutional resilience to the specific mechanisms of corruption in all its forms. Precisely in order to combat the possible lack of ethics in scientific research, in particular, and in the creation of intellectual creations, in general, the Romanian legislator has designed a tripartite system designed to ensure compliance with the rules of ethics in scientific research and to maintain society's confidence in research professionals, a system that we will analyse below.